2008
DOI: 10.1111/j.1532-849x.2008.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegrated Implants and Auricular Defects: A Case Series Study

Abstract: The survival rate for bone-anchored titanium implants and prostheses was 100%. Bone-anchored titanium implants provided the 16 patients in this study with a safe, reliable, adhesive-free method to anchor auricular prostheses with recovery of normal appearance. Under the guidance of an appropriate implant team, proper positioning of implants was optimized to allow prosthodontic rehabilitation using implant-retained prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 14 publications
3
39
0
5
Order By: Relevance
“…6,[11][12][13][14] The success criteria for craniofacial implants 15 was proposed by modifying dental implant success criteria described by Alberktsson et al 16 The clinical manifestation of osseointegration is the absence of implant mobility, both at placement and during function. Widely used clinical technique to determine craniofacial implant mobility is assessing the implant abutments manually for the presence of clinically detectable mobility by means of lateral application of pressure to the implant by two opposing instruments, and recording as positive or negative.…”
Section: Discussionmentioning
confidence: 99%
“…6,[11][12][13][14] The success criteria for craniofacial implants 15 was proposed by modifying dental implant success criteria described by Alberktsson et al 16 The clinical manifestation of osseointegration is the absence of implant mobility, both at placement and during function. Widely used clinical technique to determine craniofacial implant mobility is assessing the implant abutments manually for the presence of clinically detectable mobility by means of lateral application of pressure to the implant by two opposing instruments, and recording as positive or negative.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical studies have reported that the use of osseointegrated implants provides a satisfactory retention and improves the acceptance of auricular epithesis [12][13][14][15][16]. Further, craniofacial implants placed in the auricular region have been reported to have excellent survival rates [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the introduction of craniofacial implants, auricular epitheses were retained by using mechanical tools (spectacle frames, headbands, and steel springs), skin adhesives, or mechanical support of anatomical undercuts (when available) [1,4,13,[16][17][18]. However, skin adhesives may lead to adverse tissue reactions, discoloration and deformation at edges of the epithesis, loss of adhesion because of perspiration, and difficulties in maintaining the position of the epithesis [5,12,[16][17][18]. On the other hand, craniofacial implants offer higher retention, allow easier positioning of the epithesis, and eliminate the use of adhesives, thus extending the epithesis survival [14,20].…”
mentioning
confidence: 99%
“…(Wright et al, 2008) To distribute functional loads and reduce bending moments by avoiding the use of cantilevers or to distribute the loads if magnets were used, three implants in a nonlinear alignment are recommended. When magnets are used for retention, three implants placed in a tripod fashion could provide the best stabilization.…”
Section: Retentive Systemmentioning
confidence: 99%
“…The use of osseointegrated implants in craniofacial reconstruction has minimized some of these disadvantages and has provided patients with predictable cosmetics, improved retention, and stability of the episthesis. (Wright et al, 2008Karakoca et al, 2010, Toljanic et al, 2005, Karayazgan Saracoglu et al, 2010 Nowadays, methods of retention varied within each prosthesis type. Retention methods for auricular prostheses are bars, adhesives, magnets, and mechanical devices.…”
mentioning
confidence: 99%